Using Transitional Changes on High‐Resolution Computed Tomography to Monitor the Impact of Cyclophosphamide or Mycophenolate Mofetil on Systemic Sclerosis–Related Interstitial Lung Disease. Issue 2 (26th December 2019) - Kim, Grace Hyun J.; Tashkin, Donald P.; Lo, Pechin; Brown, Matthew S.; Volkmann, Elizabeth R.; Gjertson, David W.; Khanna, Dinesh; Elashoff, Robert M.; Tseng, Chi‐Hong; Roth, Michael D.; Goldin, Jonathan G.
Abstract : Objective: To examine changes in the extent of specific patterns of interstitial lung disease (ILD) as they transition from one pattern to another in response to immunosuppressive therapy in systemic sclerosis–related ILD (SSc‐ILD). Methods: We evaluated changes in the quantitative extent of specific lung patterns of ILD using volumetric high‐resolution computed tomography (HRCT) scans obtained at baseline and after 2 years of therapy in patients treated with either cyclophosphamide (CYC) for 1 year or mycophenolate mofetil (MMF) for 2 years in Scleroderma Lung Study II. ILD patterns included lung fibrosis, ground glass, honeycombing, and normal lung. Net change was calculated as the difference in the probability of change from one ILD pattern to another. Wilcoxon's signed rank test was used to compare the changes. Results: Forty‐seven and 50 patients had baseline and follow‐up scans in the CYC and MMF groups, respectively. Mean net improvements reflecting favorable changes from one ILD pattern to another in the whole lung in the CYC and MMF groups, respectively, were as follows: from lung fibrosis to a normal lung pattern, 21% and 19%; from a ground‐glass pattern to a normal lung pattern, 30% and 28%; and from lung fibrosis to a ground‐glass pattern, 5% and 0.5%. The mean overall improvement in transitioning from a ground‐glass pattern or lung fibrosis to a normal lung pattern was significant for both treatments (all P < 0.001). Conclusion: Significantly favorable transitions from both ground‐glass and lung fibrosis ILD patterns to a normal lung pattern were observed in patients undergoing immunosuppressive treatment for SSc‐ILD, suggesting the usefulness of examining these transitions for insights into the underlying pathobiology of treatment response.